2018
DOI: 10.1007/jhep06(2018)043
|View full text |Cite
|
Sign up to set email alerts
|

Higgs portal dark matter in non-standard cosmological histories

Abstract: A scalar particle with a relic density set by annihilations through a Higgs portal operator is a simple and minimal possibility for dark matter. However, assuming a thermal cosmological history this model is ruled out over most of parameter space by collider and direct detection constraints. We show that in theories with a non-thermal cosmological history Higgs portal dark matter is viable for a wide range of dark matter masses and values of the portal coupling, evading existing limits. In particular, we focus… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(31 citation statements)
references
References 164 publications
(215 reference statements)
0
31
0
Order By: Relevance
“…Recent studies in Refs. [22,23], have shown that in this simple framework one can both evade the current observational constraints but expect to detect a signal in the near future. However, in order to fully understand the scenario and its observational prospects, a more detailed analysis than what was conducted in Refs.…”
Section: Introductionmentioning
confidence: 85%
“…Recent studies in Refs. [22,23], have shown that in this simple framework one can both evade the current observational constraints but expect to detect a signal in the near future. However, in order to fully understand the scenario and its observational prospects, a more detailed analysis than what was conducted in Refs.…”
Section: Introductionmentioning
confidence: 85%
“…An order of magnitude estimate can be deduced by assuming an interaction of the form (the tree level coupling cancels at zero momentum transfer, so we only show the loop-induced one here) L hξξ ∼ λ 2 (4π) 2 v h ξ 2 (ξ is a DM particle). 11 For such interactions, the spin-independent cross section is approximately [53]…”
Section: )mentioning
confidence: 99%
“…The LHC data on the 125 GeV Higgs boson constrain only the coupling λ hφ if a Higgs invisible decay to ALPs is open. If produced by thermal freeze-out, ALP dark matter overcloses the universe in most of the parameter space allowed by the experimental limit on spin-independent interactions with nuclei and LHC searches for Higgs invisible decays [16]. To prevent the ALP from thermalizing with the SM plasma, one needs to make it feebly interact with the SM sector with [17] λ hφ 10 −7 .…”
Section: Higgs Portalmentioning
confidence: 99%